POLA DISTRIBUSI DAN IDENTIFIKASI JENIS BENALU PADA TUMBUHAN RUANG TERBUKA HIJAU KOTA SURABAYA - Haryanta, Dwi; Susilo, Achmadi (Universitas Nahdlatul Ulama Sidoarjo, 2018)
The beauty and benefits of plants in the Green Open Space are often disturbed by mistletoes. The existence of mistletoes often indicates the occurrence of disturbances or damage to the host plants that are parasitized. The mistletoes has been widely known by the community, but has never received attention in handling it. There has been little research on crop damage or loss caused by mistletoes. The purpose of this research is to know the existence of mistletoe and to know the pattern of distribution of mistletoe in green open space of Surabaya city. The study was conducted using the exploration method with emphasis to observe the distribution of mistletoes and identification of the type of mistletoe obtained. The results showed that the distribution of mistletoes in green open space in Surabaya tend to be grouped according to the distribution pattern of host plants. There are three types of mistletoes that mistletoe green open space plants in the city of Surabaya namely Dendrophtoe pentandra (L.) (very dominant), Macrosolen cochinchinensis (Lour.) Van Tiegh, and Henslowia frutescens.Champ